Working through layers of shame: researching and scripting black women, dwarfs, and other misfits of the Old West - Gerodimos, Roman (Interdisciplinary applications of shame/violence theory, 2022)
In this conversation, we reflect on the many layers of shame (and equal layers of resistance to shame) that we encountered while researching and scripting Black women, dwarfs and other misfits of the Old West, for the short film A Probable Outcome. A primary layer was the shame experienced by marginalised minorities paraded as “freaks” in nineteenth-century circuses and sideshows—and the counter-narrative offered by nuanced historical research producing ample evidence of pride, success and visibility. A secondary layer is the shame that we, as contemporary members of these communities, experienced while researching their history—while acknowledging our privilege and role as potential perpetrators of shaming potentially embedded in any process of handling sensitive research data or scripting the lives of others. A tertiary layer of shame is the one currently levelled against those who engage in creative work about, or representation of, people who are different from them, without direct lived experience. We engage with questions of historical accuracy and cultural context, creative freedom and lived experience, political correctness, sensitivity and representation, which have dominated public debate during the last few years, often fuelling a “cancel culture” and toxic wars on social media. We attempt to chart a path of respectful, rigorous and free artistic creation, arguing that asking the questions and trying to engage with them honestly may be more important than the answer one provides.